Faults Diagnosis in Five-Level Three-Phase Shunt Active Power Filter - L. Benyettou; T. Benslimane; O. Abdelkhalek; T. Abdelkrim; K. Bentata (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
In this paper, characteristics of open transistor faults in cascaded H-bridge five-level three-phase PWM controlled shunt active power filter are determined. Phase currents can’t be trusted as fault indicator since their waveforms are slightly changed in the presence of open transistor fault. The proposed method uses H bridges output voltages to determine the faulty phase, the faulty bridge and more precisely, the open fault transistor.